Risk Factors of Patients With Diarrhea for Having Clostridioides (Clostridium) difficile Infection - Lang, Vanessa; Gunka, Katrin; Ortlepp, Jan Rudolf; Zimmermann, Ortrud; Groß, Uwe (Frontiers in Microbiology, 2022)
Nosocomial infections with Clostridioides (Clostridium) difficile have become an emergent health threat. We sought to define risk factors for a C. difficile infection (CDI) beyond the widely known ones, such as antibiotic use and prior hospital stay. We therefore focused on a group of patients with diarrhea in order to identify risk factors for C. difficile infection among this symptomatic cohort. A total of 121 hospitalized patients from Seesen/Germany with diarrhea were included who submitted a stool sample and were interviewed about their socio-demographic background, lifestyle and state of health using a standardized questionnaire. Antibiotic potential of diuretics was examined by agar diffusion test. C. difficile was identified in 29 patients resulting in a prevalence of 24.0%. The infection was hospital-acquired in most cases (p<0.001, 82.1%; n=23/28, versus 29/91, 31.9%). The generally accepted risk factor previous antibiotic use was confirmed in this study (p=0.002, n=23/28 CDI patients, 82.1%, versus n=44/91 non-CDI patients, 48.4%). The following additional risk factors were identified: regular consumption of proton pump inhibitors; PPI (p=0.011, n=24/29, 82.8% vs. n=52/92, 56.5%), CDI patients ate less vegetables (p=0.001, n=12/29, 41.4% vs. 69/92, 75.0%). The intake of the diuretic agent torasemid in patients with CDI (p=0.005, n=18/29, 62.1%) was higher than in patients without (n=30/92, 32.6%). More patients with CDI had to undergo a surgery in the previous year (p=0.022, n=13/29, 44.8% vs. n=21/92, 22.8%) and held more birds (p=0.056, n=4/29, 13.8%) than individuals of the negative group (n=3/92, 3.3%). In conclusion, although no antibiotic potential was detected in diuretics, especially torasemid seems to have significant influence for the occurrence of a CDI as well as a nutrition poor in vegetables. A diet rich in vegetables represented a fourfold lower risk for a CDI (OR 0.240, CI [0.0720 - 0.796]).